ID-based efficient and proactive threshold proxy signature in the standard model - YU Yi-ke1; ZHENG Xue-feng2 (Tongxin xuebao)
The security of existing identity-based threshold proxy signature schemes were almost proven in the random oracle model,and each proxy signer’s proxy signature key was fixed in the valid period.A（t,n） ID-based proactive threshold proxy signature scheme（IBTPTS） was presented by using the publicly verifiable secret sharing technology,based on existential identity-based signature scheme.The scheme was proved to be safe in the standard model.Each proxy signer’s proxy signature key can be updated regularly,and proxy signature verifying procedure only needs const bi-linear pairings.Therefore the scheme has better dynamic security and higher efficiency.